Farmácias magistrais de Goiânia. Análise de não conformidades e penalidades aplicadas - Oliveira, Adriana Delcy de (2017)
The growing need for medicines as well as the growth of pharmaceutical activity drive the quest for quality. Various process control actions and finished products are constantly reviewed. The actions of health surveillance are associated to the process of regulation, monitoring and inspection of products and services, in order to prevent and reduce risks to individual and collective health in the area of surveillance. The objective of this study was to characterize and quantify the penalties of fine, seizure, interdiction and warnings in magical pharmacies in Goiânia. The methodology used was quantitative, retrospective and analytical, with an evaluation of the relationship between the number of pharmacists, self inspection number, pharmaceutical owner and affiliation, and the number of penalties issued. The Kruskall Wallis and Chi square tests were applied. Data were obtained from the database of the Sanitary Surveillance of Goiânia and sanitary inspections that were carried out in accordance with the Resolution of the Collegiate Board of Directors (RDC) 67/07, which deals with good practices of manipulation of magisterial preparations and For human use in pharmacies. The independent variables (number of pharmacists, number of self-inspections, affiliation or not with a class institution, ownership of a pharmacist and dependents (number of fines, seizures, prohibitions and warnings planned in the survey) were reported. Of pharmacists favors the quality of work performed, that pharmacies that performed self-inspection had a low incidence of occurrence of non-conformities (suffered a lower number of fines), pharmacies affiliated to class institutions suffered a smaller number of prohibitions and that the fact The owner being a pharmacist influenced a smaller number of penalties. The study pointed out that the lower the number of assessments, seizures and prohibitions separately, the lower the total number of penalties.